# SOLUTION: Rewrite each equation in vertex form. Then sketch the graph. 19. a. y=4x^2+8x-4 b. y=-3x^2-4x-1 c. y=-5x^2=10x+1 d. y=-2x^2+10x-11 e. y=3x^2+9x+6

Algebra ->  Linear-equations -> SOLUTION: Rewrite each equation in vertex form. Then sketch the graph. 19. a. y=4x^2+8x-4 b. y=-3x^2-4x-1 c. y=-5x^2=10x+1 d. y=-2x^2+10x-11 e. y=3x^2+9x+6      Log On

 Question 83113: Rewrite each equation in vertex form. Then sketch the graph. 19. a. y=4x^2+8x-4 b. y=-3x^2-4x-1 c. y=-5x^2=10x+1 d. y=-2x^2+10x-11 e. y=3x^2+9x+6 Answer by Edwin McCravy(13211)   (Show Source): You can put this solution on YOUR website! ``` a. y=4x^2+8x-4 answer: y = 4(x+1)²-8 b. y=-3x^2-4x-1 answer: y = -3 + c. y=-5x^2+10x+1 answer: y = 5(x-1)²+6 d. y=-2x^2+10x-11 answer: y = -2(x-5/2)²+3/2 e. y=3x^2+9x+6 answer: y = -3 - I'll do (b) only. The others are the same. y = -3x² - 4x - 1 Factor the coefficient of x² out of the first two terms. (Do not factor out x with it) y = -3(x² + x) - 1 To the side multiply by , getting Square getting Add and then subtract inside the parentheses: y = -3(x² + x + - ) - 1 Change the parentheses to brackets so parentheses may be inserted: y = -3[x² + x + - ] - 1 Factor the first three terms in the brackets as a perfect square: y = -3[ - ] - 1 Remove the bracket by distributing the -3, remembering to leave the intact: y = -3 + - 1 Write the 1 as y = -3 + - y = -3 + Now plot the vertex (,) Find the x-intercepts by setting y = 0 y = -3x² - 4x - 1 0 = -3x² - 4x - 1 3x² + 4x + 1 = 0 (3x + 1)(x + 1) = 0 3x + 1 = 0 x + 1 = 0 3x = -1 x = -1 x = So the x intercepts are (,0) and (-1,0) Plot them. Find the y-intercept by letting x = 0 in the original y = -3x² - 4x - 1 y = -3(0)² -4(0) - 1 y = 0 - 4 - 1 y = -1 So plot the y-intercept (0.-1) too Now draw a smooth parabola through those 4 points: Edwin```